Isolation and Identification of Indigenous Cellulolytic Bacteria from Sago Pith Waste at Palopo, South Sulawesi, Indonesia - Faizah, Mamluatul; Ardyati, Tri; Suharjono, Suharjono (Graduate School, Universitas Brawijaya, 2020)
Palopo, South Sulawesi, is one of the traditional industrial centers of sago processing. The accumulation of sago pith waste around industrial sites can pollute the environment. Some microorganisms can degrade the cellulose in sago pith waste. This study was aimed to evaluate the indigenous cellulolytic bacteria from sago pith waste as a biodegradation agent. Bacteria were isolated from sago pith waste and grown on a 1% Carboxyl methyl cellulose (CMC) agar medium. The cellulolytic activity was analyzed semiquantitatively using 1% Congo red and quantitatively using the 3,5-Dinitrosalicylic Acid (DNS) method at pH variations of 4, 5, and 6. The potential isolate was identified based on 16S rDNA sequence similarity. This study obtained 21 bacterial isolates where six isolates were A1D, A1E, A1I, A1K, A2A, and B1A had the highest cellulolytic index at 0.82 - 1.13. Among those six isolates, the A1E isolate had the highest cellulolytic activity, 0.54 U.mL-1 at pH 6. The isolate A1E was identified as Burkholderia cepacia JCM 2799 with 99.73% similarity of 16S rDNA sequence. Keywords: Burkholderia cepacia, cellulolytic bacteria, cellulase enzyme, sago waste.